PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL - Sarah Isnaeni; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This research starts from the emergence of problems experienced directly by the author during the learning process, namely the low ability of students to connect to the material in One Variable Equations and Linear Inequalities. The approach chosen by the author is a contextual approach, which starts from the things that are real in everyday life and emphasizes the process skills of doing mathematics. While the research method used is classroom action research (PTK), which combines research procedures with substantive action, which seeks to review and reflect on a learning model with the aim of improving quality (both process and product) of learning. This study consists of two cycles. Each cycle consists of planning, action, observation and evaluation and reflection. The instruments used are learning instruments (RPP and LKS) and data collection instruments consisting of test instruments (formative tests and sub-summative tests) and non-test instruments ( observation sheet, student journal, questionnaire and interview). This study aims to determine the connection ability of students of class VII-C SMP in Bandung after getting learning with contextual approaches, and student responses to learning with contextual approaches. The results of the study showed an increase in connection skills and positive responses of students of class VII-C. this can be seen from the results of the formative tests which showed a significant increase between cycles. Students also give a positive response to this learning. This can be seen from the attitude of those who are enthusiastic in participating in learning with a contextual approach. Students who were initially lacking in attention, gradually turned to concentration, because they felt happy about this contextual approach. In working groups of students also seemed enthusiastic about discussing with friends. This indicates a positive response from students to the contextual approach